Strategies for Translating Swearing Expressions found in Seperti Dendam, Rindu Harus Dibayar Tuntas into English - Yosafat Barona Valentino (Prologue: Journal on Language and Literature, 2023)
This article examines swear word translation in Eka Kurniawan's Indonesian novel, Seperti Dendam, and its English version, Vengeance. The study analyzes swearing expressions and translation strategies using a qualitative approach. Data from both novels reveals seventeen swear words across eight themes. Swear words are classified into four function types and a mixed function. The translator employed five main strategies, maintaining function and theme being the most common. The findings show the translator aimed to preserve the original function and theme while adapting to the target text's style. Indonesian swear words share similarities with English counterparts in function and theme.